Empowerment knowledge of elementary school teachers for supporting green schools - Ilmi Zajuli Ichsan; Santhi Pertiwi; Yudi Hermawan (Universitas Muhammadiyah Malang, 2023)
Environmental problems including in this case environmental pollution need to be overcome in various ways. Schools as educational institutions need to be examples and role models for the development of environmental-based schools or green schools. The problems that occurred in one of the schools, namely SDS Darul Amal Jampangkulon Sukabumi West Java showed that information related to green schools was still very minimal. The purpose of this activity is to overcome the problem of the low knowledge of elementary school teachers related to efforts to establish green schools. The implementation method used in this activity is through online seminars using a teleconference application. The results of this community service activity indicate that the knowledge score and teacher attitudes have increased related to green school. The average knowledge score at the beginning was 24.79 and increased to 32.62 and teacher attitudes increased from 82.92 to 86.67 for the topic of green school. Green school activities that can be applied in future activities are to familiarize students with being able to sort waste.